Zoonoses Tuberculosis Risk from Non-Human-Primate Trade and Movement: Preventive Measure Perspective - Bagus Priastomo, Indra; Budi Susilo, Puguh (Dinasti Research, 2024)
The trade in non-human primates (NHPs) is economically profitable in both local and global markets. However, it also poses a significant threat of disease transmission between NHPs and humans, particularly zoonotic tuberculosis, which is frequently reported in NHPs. Due to the high similarity between NHPs and humans, they share many pathogens. As a potential hub for NHP trade, Indonesia needs to enhance its knowledge and preventive measures to manage tuberculosis transmission related to NHPs trade and movement. Legislation at both international and national levels has been established to address the prevention of tuberculosis infection from NHPs. In addition to legislative measures, effective prevention also relies on implementing screening and detection protocols, as well as maintaining good biosecurity practices during handling NHPs.